Chi's sweet adventures. 4 - Natsume, Kinoko; Konami, Kanata, 1958- (Vertial Comics, 2019)
Includes a collection of comics featuring a kitten named Chi and his family and friends. Here Chi runs away, visits the ocean, and copes with loneliness.